Formulation, Developing, and Assessment of Vitamin D3-Enriched Microsphere Cream for Anti-Aging Therapy - Girivasan, Shyam Nikethen; Salam, Sabeel; Musthafa, Mohammed Fazil Rayamarakkarveettil; Peedikayil, Zakir Hussain Kovval; Reji, Akza Marium; Venkatesan, Manojkumar (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: The aim of this paper is to describe the advancement in dermal drug delivery employing microspheres as the method, focusing on the synthesis of microspheres by solvent evaporation technique to be formulated in to a cream base foundation. Materials and Methods: The microspheres were prepared through a solvent evaporation method followed by incorporation into a cream base enriched with Vitamin D3 (Cholecalciferol) to improve the drug release rate. In vitro/ex vivo analytical practices were used to assess the permeation of the drug, with specific emphasis of the capability of the formulation of delivering the drugs across a membrane. Results: Ex vivo diffusion studies suggested the drug release kinetic followed zero order model, implying controlled and sustained release of the active compound. Additional characterization using FTIR spectroscopy revealed the absence of physical and chemical incompatibilities between the drug and formulation ingredients which enhance the stability of the product. Conclusion: Therefore a Vitamin D3 Anti-Aging Cream in the microsphere formulation demonstrates a great potential to be safe, efficacious and non-irritating drug delivery system. From this view, it is believed that this approach will reduce side effects of topical applications to a minimal level while at the same time enhancing therapeutic efficiency which will give an improvement of future topical drug delivery method in anti-aging therapies.
Keywords: Anti-aging; Cosmetics; Microsphere; Skin Care; Vitamin D3